The nexus of Nusantara archipelagic cultural values in pupil management and its activities on social harmony through national identity revitalization - Redjeki, Dwi Sogi Sri; Imron, Ali; Rasdiana, Rasdiana; Wiyono, Bambang Budi; Prestiadi, Dedi; Wahed, Andi; Purwati, Endang; Dami, Zummy Anselmus; Margariena, Ika Nova; Maulina, Sasi; Sinon, Iriwi Louisa S. (Frontiers in Education, 2025)
Building on Anderson’s nationalism concept (2006), national culture is essential as it shapes social practices and institutions; however, its complexity arises from internal diversity. This research aims to clarify how Nusantara cultural values are integrated into pupils’ management and activities to revitalize national identity and promote social harmony in Indonesia’s multicultural context. Utilizing a cross-sectional design, data were collected through surveys from 265 participants, including school leaders, teachers, staff, and pupils across ten provinces. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed for data analysis, revealing significant relationships among the variables. The findings indicate that the integration of Nusantara cultural values positively influences social harmony and significantly impacts the revitalization of national identity. Furthermore, pupil management activities grounded in these cultural values enhance social harmony and positively affect national identity, with the latter significantly influencing social harmony. This demonstrates a complex interplay among these elements, where both cultural value integration and pupil management activities are pivotal, with national identity acting as a mediating factor. These results underscore the critical role of cultural values in shaping educational experiences and fostering unity amid globalization. The implications of this study suggest practical strategies for educators and policymakers to enhance cultural integration within schools, preserving Indonesia’s rich heritage while promoting inclusivity. Ultimately, this research contributes to the discourse on cultural education, offering a framework for future studies to strengthen national unity and intercultural understanding in diverse societies.